Performance Analysis of Finger Flexor and Finger Extensor Muscles on Wall Climbing Athletes through Electromyography Measurement, Handgrip Strength, Handgrip Endurance and Lactate Acid - H Susanti; Suprijanto Suprijanto; Farida I. Muchtadi; T Apriantono (Jurnal Otomasi Kontrol dan Instrumentasi, 2009)
One of activities involved gripping activity is wall climbing sport. Physiologically, gripping activity involves finger flexor and finger extensor muscles at the lower arm. Naturally, muscles performance will decrease if muscles are given static or dynamic weight during certain time. This performance decrease is related with fatigue condition, which is also related with lactate acid accumulation, insufficient of metabolic reserve, and the decrease of neural activity in stimulating contraction[2].  Muscle fatigue characteristic experienced by participants were observed from the changing trend of Power Spectral Density (PSD) and median frequency of EMG signals, lactate acid level, and changing of handgrip strength and handgrip endurance values from four groups of measurement data.  The experiment was involving two professional wall climbing athletes as participants. The measurements were performed four times, which were before and soon after climbing, after first 15 minutes and after the second 15 minutes active recovery process, except for lactate acid level, measurements were performed twice, which were before and soon after climb activity. The athlete would have been ordered to climb the boulder for 15 minutes with a certain difficulty level.  Muscle performance measurement involved in this gripping activity was very important to know how far the influence of difference of subject and period of active recovery to recover muscle condition. By this knowledge, a couch or an athlete can arrange an effective training strategy to reach a maximum achievement.  Keywords: Electromyography, handgrip endurance, handgrip strength, Power Spectral Density, median frequency, finger flexor and finger extensor, lactate acid, fatigue